Spiegare i passaggi.
Svolgere SENZA la tecnica X sostituzione.
Spiegare i passaggi.
Svolgere SENZA la tecnica X sostituzione.
a.
$ \int \frac {1}{1+(x^n)^2} \cdot x^{n-1} \, dx = $
Rendiamolo immediato
$ \frac{1}{n} \int \frac {1}{1+(x^n)^2} \cdot n \cdot x^{n-1} \, dx = $
è l'immediato dell'arcotangente
$ = \frac{1}{n} arctan(x^n) + c $
b.
La derivata di $ 1+x^{2n} = 2n \cdot x^{2n-1} $
rendiamolo immediato
$ \frac{1}{2n} \int \frac {2n \cdot x^{2n-1}}{1 + x^{2n}} \, dx = $
$ = \frac{ln(1+x^{2n})}{2n} + c $